Media Pembelajaran Seks Untuk Remaja (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
This research was based on social unrest that occurred among adolescents. Many deviations occur around where we live such as sexual deviations. Lifestyle of adolescents today who have the mindset of free life. The author makes this interactive work to help learn teens and parents to make it easier to educate their children at home with an attractive appearance so it is not boring. So it can be useful for adolescents as well as making them aware of sexual deviations. Material about sex education for adolescents is available in the 2013 Middle School Class 2 Middle School Curriculum on Sociology and Biology as well as the Education Unit Level Curriculum (KTSP) on Integrated Social Sciences (IPS) subjects. Based on studies of similar product trends there has not been found any interactive media of sex education material for teenagers. Therefore the focus of the work in this thesis is to create interactive media that have educational value, namely the development of adolescents, biologically, socially, and sexually transmitted diseases. The technique applied is flash-based digital computerization with realist illustration style. The interactive media user segment is aimed at students so that the material becomes easier to understand and increases the ability to think up to the High Order Thinking Skills (HOTS) stage, which is creating according to Bloom's Taxonomy theory.